2003
DOI: 10.1016/s0921-8890(02)00380-9
|View full text |Cite
|
Sign up to set email alerts
|

Robota: Clever toy and educational tool

Abstract: Therapeutic and educational applications of robots have created a demand for robots showing a number of social skills. These skills include the capacity to imitate, to learn from demonstration, to interpret gestures and to recognize speech. Robot toys are an ideal platform to investigate the potential and limitations of human-robot social interactions. This paper presents Robota, a mini-humanoid doll-shaped robot. Robota is used in an introductory robotics class at the undergraduate level. The class offers an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 13 publications
0
58
0
Order By: Relevance
“…For instance, Billard, Robins, Nadel and Dautenhahn [10] found that children with ASD responded positively to a doll-like robot with a mechanical-looking body but a humanlike face and avoided looking at the robot's face to a lesser extent than reported in Robins et al's [45] study. Moreover, the robot used in Billard et al's study provoked comparable responses from children with ASD to responses triggered by a non-humanoid, completely mechanical-looking robot [9]. These findings suggest that an appropriate combination of humanlike and mechanical features in the appearance of the robots used in treatment programs is important to children with ASD [12].…”
Section: Introductionmentioning
confidence: 75%
“…For instance, Billard, Robins, Nadel and Dautenhahn [10] found that children with ASD responded positively to a doll-like robot with a mechanical-looking body but a humanlike face and avoided looking at the robot's face to a lesser extent than reported in Robins et al's [45] study. Moreover, the robot used in Billard et al's study provoked comparable responses from children with ASD to responses triggered by a non-humanoid, completely mechanical-looking robot [9]. These findings suggest that an appropriate combination of humanlike and mechanical features in the appearance of the robots used in treatment programs is important to children with ASD [12].…”
Section: Introductionmentioning
confidence: 75%
“…Robotic toys tend to be more democratised and the scientific community is working on their usage as an educational and therapeutic tool (Billard, 2003). Robins and Dautenhahn (Robins and Dautenhahn, 2007) have especially shown that their use encourages the interactions among autistic children.…”
Section: Motivationsmentioning
confidence: 99%
“…But as each human is different, the social skills needed to maintain the attention in the human/toy interaction requires the toys to be able to self-adapt to anybody (Huang, 2010). To this extent, an interesting approach is the Imitation Learning (Billard, 2003) (Robins and Dautenhahn, 2007). Imitation Learning is a form of Learning from Demonstration, a paradigm mainly studied in robotics allowing a system to acquire new behaviors from the observation of human activity (Argall et al, 2009).…”
Section: Motivationsmentioning
confidence: 99%
“…Robota has the capability to connect to an array of various sensors, and to support a spectrum of multi modal interactions with children. For a complete description of Robota's hardware see [18]. The robot's features of speech processing, learning and motion tracking were not used in current trials and its operation and behaviour have been greatly simplified.…”
Section: A the Robotmentioning
confidence: 99%